2018
DOI: 10.1111/jora.12403
|View full text |Cite
|
Sign up to set email alerts
|

Latent Profiles of Discrimination and Socialization Predicting Ethnic Identity and Well‐Being Among Asian American Adolescents

Abstract: Ethnic identity is rooted in sociocultural processes, but little is known about how social interactions predict its longitudinal changes. Using data from 154 Asian American adolescents, latent profile analysis derived four typologies based on unfair treatment (i.e., discrimination, model minority stereotyping) and ethnic socialization (i.e., cultural socialization, preparation for bias, promotion of mistrust): Low Cultural Salience, High Cultural Salience with Marginalization, Culturally Prepared with Low Mist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 59 publications
4
45
0
1
Order By: Relevance
“…Bivariate correlations indicated that participants who identified strongly with the heritage culture also identified more strongly with the mainstream culture. This reflects that the majority of participants identified with both the heritage and mainstream culture (dual-mainstream identifiers), but may also be an indication of cultural salience, meaning that participants generally found cultural identities a more or less important part of their self-identification (Kiang, Supple, and Stein 2018). Correlations further indicated that girls were more likely to report a more developed heritage identity and lower life satisfaction than boys.…”
Section: Preliminary Analysesmentioning
confidence: 95%
“…Bivariate correlations indicated that participants who identified strongly with the heritage culture also identified more strongly with the mainstream culture. This reflects that the majority of participants identified with both the heritage and mainstream culture (dual-mainstream identifiers), but may also be an indication of cultural salience, meaning that participants generally found cultural identities a more or less important part of their self-identification (Kiang, Supple, and Stein 2018). Correlations further indicated that girls were more likely to report a more developed heritage identity and lower life satisfaction than boys.…”
Section: Preliminary Analysesmentioning
confidence: 95%
“…In addition, several studies reported null associations (e.g., Huynh & Fuligni, ), and only a couple found it to be associated with positive adjustment (i.e., Nelson, Syed, Tran, Hu, & Lee, ; Thai, Lyons, Lee, & Iwasaki, ). Furthermore, findings from two studies suggested that the links between the promotion of mistrust strategy and adjustment may be context dependent because the association varied based on whether the promotion of mistrust strategy was used in tandem with other strategies (Kiang, Supple, & Stein, ) or whether individuals' personal values were consistent with this socialization strategy (Tran, ). In the collection of studies, however, there was limited evidence that the promotion of mistrust strategy was associated with positive outcomes, and the most consistent evidence suggested that higher levels of engagement in the promotion of mistrust socialization were associated with greater youth maladjustment.…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
“…More than a third of all studies examined preparation for bias as a socialization strategy (see Table ). Contrary to the promotion of mistrust strategy, preparation for bias was often theorized to promote positive adjustment among youth because this strategy was expected to prepare youth for potential discrimination while providing strategies for how to cope (e.g., Atkin et al, ), and such coping skills were hypothesized to be beneficial for youths' adjustment (e.g., Kiang et al, ; Neblett et al, ). Findings, however, were considerably mixed, making it difficult to draw clear conclusions regarding the links between preparation for bias and youth adjustment (see Table ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions of ethnic discrimination are likely a covariate for the link between adolescents' perceived acculturation expectations and acculturation orientations. Latent profile analysis has recently linked perceiving ethnic discrimination to parents' ethnic-racial socialization over time (Kiang, Supple, & Stein, 2018). The authors argued that perceiving high amounts of ethnic-racial socialization at home may increase adolescents' awareness of cultural issues outside of home, including a higher perception of ethnic discrimination.…”
Section: Acculturation Expectations By Parents and In School And Ethmentioning
confidence: 99%